1998
DOI: 10.1046/j.1365-3148.1998.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of FFP: results of a retrospective process and outcome audit

Abstract: An audit has been carried out on the usage of 216 units of fresh frozen plasma (FFP) issued to 41 patients. This involved the systems of FFP issue, the appropriateness of prescription as well as the recorded benefits. Sixty-six per cent of the initial requests for FFP appeared to satisfy criteria for appropriate use. Review of the case notes resulted in some changes to earlier decisions and a slight increase to 73% of those accepted as valid. Only 94% of the FFP issued could be proved to have been given to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
3
10
1
Order By: Relevance
“…In our study, ICU and surgical teams were just as likely to order inappropriate FFP transfusions. Our findings are consistent with previous research (4,5,6,18,19), including some in the critically ill (20,21). Rao and colleagues (20) found that Ͼ20% of critically ill patients are exposed to FFP and that about 40% had high prothrombin time (twice the normal level) as the sole indication for FFP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, ICU and surgical teams were just as likely to order inappropriate FFP transfusions. Our findings are consistent with previous research (4,5,6,18,19), including some in the critically ill (20,21). Rao and colleagues (20) found that Ͼ20% of critically ill patients are exposed to FFP and that about 40% had high prothrombin time (twice the normal level) as the sole indication for FFP.…”
Section: Discussionsupporting
confidence: 92%
“…Because our focus was on patients receiving FFP, we did not review bleeding or invasive procedures among patients who did not receive FFP. Although our results are consistent with others (4,5,6,18,19), they represent practices in one ICU and may not be appropriate for generalization. However, our results are likely to be valid.…”
Section: Discussioncontrasting
confidence: 55%
“…However, clinical practice is characterized by considerable variation in the use of FFP (Sanguis Study Group, 1994). Local audits of FFP use in different hospitals in the UK suggest that only around 60% of transfusions were compliant with recommendations in guidelines and in many cases the doses given were below those recommended (Jones et al , 1998; Eagleton et al , 2000; Stainsby & Burrowes‐King, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In our own region, use of FFP has grown at 2% annually for the past 5 years. In addition, published studies often show unjustifiable use of FFP (Thomson et al ., 1991; Jones et al ., 1998). Concerningly, rates of inappropriate use may be higher in UK than elsewhere (Brien et al ., 1989; Nicholls et al ., 1994; Metz et al ., 1995).…”
mentioning
confidence: 99%